N‐Formylation of Amines with CO2 and H2 by Using NHC–Iridium Coordination Assemblies as Solid Molecular Catalysts. Issue 20 (7th August 2018) - Zhang, Yang; Wang, Jiaquan; Zhu, Haibo; Tu, Tao
Abstract: One of the NHC–iridium coordination assemblies containing 1, 5‐cyclooctadiene (COD) and iodide ion has been demonstrated as robust, efficient, recyclable solid molecular catalyst for N‐formylation of diverse primary and secondary amines with CO2 and H2 under mild reaction conditions. Remarkably, in the case of N, N ‐dimethylformamide production, even at 0.1 mol % catalyst loading under solvent‐free conditions, the solid catalyst can be readily recovered by simply filtration and reused more than 10 runs without noticeable loss of activity. Abstract : One of the NHC–iridium coordination assemblies containing 1, 5‐cyclooctadiene (COD) and iodide ion has been demonstrated as a robust, efficient and recyclable solid molecular catalyst for N‐formylation of various primary and secondary amines with H2 and CO2 under mild reaction conditions at catalyst loadings as low as 0.1 mol %.